STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN PADA PELAKU UMKM RUMAHAN OLIVE CAKE N COOKIES BENGKAYANG - Tri Purwani; Yoseph Erbito; Nur Afifah (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The right marketing strategy is very important to increase sales and growth of home-based MSMEs. By implementing an effective marketing strategy, MSMEs can increase product visibility, attract new customers, and maintain customer loyalty. The study used a qualitative method, with a qualitative descriptive approach. Research data were obtained from the results of primary data and secondary data using several data collection techniques such as observation, interviews, and documentation studies. Based on the results of the study, sales of Olive Cake n Cookies products have increased since they first marketed their products until now. Thus, the marketing strategy that can be applied by Olive Cake n Cookies is a strategy in the marketing mix, namely product, price, place, promotion that can increase sales of Olive Cake n Cookies products.